EFFET DE L’ÉPURATION PAR ÉLECTROCOAGULATION SUR LA POLLUTION DES EFFLUENTS DE L’HÔPITAL MOHAMED V DE MEKNÈS - Nour-eddine, Ameziane; Abdelaziz, Khennoussi; Lahcen, Benaabidate (European Scientific Journal, ESJ, 2013)
The effluents of the Mohamed V hospital of Meknes include strong polluting factors harmful to environment and to human health, notably important bacterial load. This hospital has not a pretreatment station so it rejects its effluents in the urban sewer system without any preliminary treatment. The urban effluents are cleared open air at the level of the Aïn Choubbik district and poured into Bourouh river notably during pluvial period; consequently they cause a physicochemical and biological deterioration of the aquatic ecosystem. To reduce their negative impacts, several treatment techniques are operated. The chemical coagulation and the biological treatments are techniques used particularly for the treatment of various types of effluents. Their inconveniences it is because they cause an acidification of treated water and a production of important quantities of muck. The electrocoagulation is a very interesting alternative to these techniques. The present job registers as part of research works which have as objective to study the effects of this technique on wastewaters of the Mohamed V hospital of Meknes. This is the way how we studied experimentally the treatment of the hospital effluents by the means of the electrocoagulation by using iron electrodes. To determine the optimal conditions of treatment of these effluents, we made several experiments by varying every time the intensity of current and time of retention. The obtained rates of reduction are very important, they reached 79,21 % for COD, 93,76 for suspended matter and 97,33 % for the fecal coliformes.